Extramedullar plasmocytoma of the oral cavity - Olugbeje Helen; Fourcade Arthur (EDP Sciences, 2020)
Introduction: Extramedullar plasmocytoma (EMP) is a plasma cell disease, such as solitary plasmocytoma of the bone and multiple myeloma. It is developed in the soft tissues. Observation: A 79-year-old patient consulted for a painful tumefaction of the gum associated to a radiolucent area on the right side of the mandible on the panoramic x-ray. After surgical enucleation, histological examination showed that the diagnosis was either an IgA extramedullar plasmocytoma or a multiple myeloma. The spreading assessment eliminated the diagnosis of multiple myeloma. The patient was then treated with radiotherapy. Discussion: EMP is a rare tumoral disease. Few cases described oral localisation. The main differential diagnosis, that must be excluded is multiple myeloma. Transformation in multiple myeloma exists. The first intention treatment is radiotherapy of the lesion. Conclusion: EMP of the oral cavity is very rare. After treatment, follow-up is required to detect second localisation or progression in multiple myeloma.